Polish Underground Extracts, no. 11 (1984) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. The Concept of Economic Reform / by Rafał Krawczyk[from: Krawczyk, Rafał. The Meaning of "Reform." Warszawa: Wydawnictwo, 1984.]"The Meaning of 'Reform'," published as a separate booklet, is actually the first chapter of a longer book, "A Short History of Reforming the Economy," by Rafał Krawczyk. During the Solidarity period, Krawczyk was Secretary-General of the Polish Economic Society and represented the trend in favor of a radical reform of the economy, which, he believed, should be run on pragmatic lines. With the imposition of martial law he was ousted from his post. "The Meaning of 'Reform' " has been issued by a Warsaw underground publishing house, Wydawnictwo, without the author's knowledge. Sanctions, Western Aid, Political Conditions[from: Tygodnik Mazowsze, no. 98 (6 September 1984)]The leading Solidarity weekly for the Warsaw region considers the effects of Western sanctions on the Polish economy, and while rejecting official figures on the losses resulting from them (which cannot be calculated precisely) it agrees that the economy can only be saved with help from abroad. The International Monetary Fund and the Economic Reform[from: Tygodnik Mazowsze, no. 99 (20 September 1984)]This article comments on an aspect of possible economic reform in Poland as outlined in the previous issue of this Warsaw region Solidarity weekly Those Disgusting Private Dealers / by Jan Malinowski[from: Niepodległość, no. 29 (May 1984)]This article from the monthly "Independence," written under a pseudonym and carrying an ironic title, explains the difficulties created by the state commercial system for anyone who wants to engage in private enterprise, even on the most limited scale. Added to this is the fact that some private entrepreneurs do manage to prosper, but since the "market" price of their product is sometimes excessive, they often face ambivalent reactions from the public. A System Hostile to Nature[from: KOS, no. 59 (3 September 1984)]"KOS" is the biweekly underground paper of the Committee of Social Resistance. It has been appearing in Warsaw since the imposition of martial law. This article deals with the potentially catastrophic environmental problems currently facing Poland. A Point of View[from: Solidarność Gdańsk, no. 13(115) (20 August 1984)]The periodical "Solidarność Gdańsk" is the successor to the paper of the Gdańsk Interfactory Founding Committee of Solidarity; its first issue appeared in the Gdańsk shipyards on 23 August 1980. Since martial law was imposed the paper has been appearing regularly and over 50 issues have appeared since January 1982. This item is a surprising piece of journalism; it is an interview conducted with the manager of an unspecified enterprise specifically for the underground press. The fact that he should have agreed to this is important in itself.